Plant immune receptors interact with hemibiotrophic pathogens to activate plant immunity - Zhou, Diao; Chen, Xingzhou; Chen, Xinggang; Xia, Yandong; Liu, Junang; Zhou, Guoying (Frontiers in Microbiology, 2023)
Phytopathogens pose a devastating threat to the productivity and yield of crops by causing destructive plant diseases in natural and agricultural environments. Hemibiotrophic pathogens have a variable-length biotrophic phase before turning to necrosis and are among the most invasive plant pathogens. Plant resistance to hemibiotrophic pathogens relies mainly on the activation of innate immune responses. These responses are typically initiated after the plant plasma membrane and various plant immune receptors detect immunogenic signals associated with pathogen infection.Hemibiotrophic pathogens evade pathogen-triggered immunity by masking themselves in an arms race while also enhancing or manipulating other receptors to promote virulence. However, our understanding of plant immune defenses against hemibiotrophic pathogens is highly limited due to the intricate infection mechanisms. In this review, we summarize the strategies that different hemibiotrophic pathogens interact with host immune receptors to activate plant immunity. We also discuss the significant role of the plasma membrane in plant immune responses, as well as the current obstacles and potential future research directions in this field. This will enable a more comprehensive understanding of the pathogenicity of hemibiotrophic pathogens and how distinct plant immune receptors oppose them, delivering valuable data for the prevention and management of plant diseases.